THERMAL-STRUCTURE COUPLING ANALYSIS OF HOLLOW CYLINDRICAL ROLLER BEARING FOR CONE BIT - HAN ChuanJun; Li Ying; ZHANG Jie; YAN JiaWei (Jixie qiangdu, 2016)
Based on the bearing contact mechanics and heat transfer theory,thermal-structure coupling model of hollow cylindrical roller bearing for cone bit was established. Temperature,stress and deformation distribution of the bearing were analyzed,and influences of parameters on bearing’s thermal-structure coupling field were studied,such as hollow ratio,bit pressure,friction factor,revolving speed,grease temperature and well temperature. The results show that the maximum temperature of bit’s hollow cylindrical roller bearing system appears on the thrust bearing,the maximum equivalent stress occurs on the tooth claw journal,the maximum displacement occurs on the cone,and the maximum contact stress occurs on the hollow roller contact pair. With the increasing of hollow ratio,the maximum temperature,contact stress and deformation of the hollow roller gradually reduce,while the maximum equivalent stress decrease firstly and then increase. The equivalent stress of the hollow roller with hollow ratio 55% is minimal. Temperature,stress and deformation of the bearing parts increase with the increasing of drilling pressure,friction factor,revolving speed,grease temperature and well temperature. These results can provide useful references in designing and optimizing the bearing of cone bit,and benefit the application of cone bit in high temperature deep well.